Types of Language Styles Used By Tobi “Tobiwan” Dawson in His Twitch Channel - Vinsensius Wijaya (STBA Prayoga Padang, 2021)
Abstract People may use a different kinds of language styles in their social media. The use of language styles has a purpose, whether to persuade others, to share news, or even to intimate people. According to this issue, this research aims to analyze the types of language styles found in the utterances of Tobi Dawson. In the research, the writer applied the qualitative method. The data in this thesis are in form of utterances of Tobi Dawson in his twitch channel that had been transcribed. The answers the problem of the part of language style, the researcher answered by using Joos’ theory of types of language style and Badiah’s function of language style. The findings of this research showed that there are two most styles used by Tobi Dawson in his video; casual and intimate style, caused by the participants who influenced Tobi Dawson to use it more. Therefore Tobi Dawson used the styles for daily conversation and used spontaneous sentences.